A Multi-homing Seamless Vertical Handoff Protocol for integrated UMTS/WLAN network - Rizvi, S. (IEEE Computer Society, 2014)
Nowadays, the wireless devices are equipped with multiple network interfaces to support different wireless technologies, for example, Universal Mobile Telecommunications System (UMTS), Wireless Local Area Network (WLAN), and Bluetooth etc. However, while increasing the options to connect internet via different access networks, seamless mobility cannot be assured when the wireless device is roaming across heterogeneous wireless access domains. This limitation appears because multiple wireless interfaces cannot be utilized simultaneously for the same data session. Due to the enormous number of Internet Service Providers (ISPs) and the fragmented nature of wireless technologies, the wireless devices must support multiple wireless access networks concurrently. If more than one wireless interface is utilized for the internet connectivity then seamless mobility without any service degradation can be attained. The literature illustrates that most of the existing internetworking techniques are lacking to provide the seamless mobility. In this paper, we have proposed a Multi-homing Seamless Vertical Handoff Protocol (MSVHOP) for the seamless switching of active data session between UMTS and WLAN networks. In order to decrease the vertical handoff delay and transient lost information, the MSVHOP implements multi-homing feature in the proposed internetworking mechanism that leads to attain the less signaling and node processing cost during handoff. Â© 2014 IEEE.